2011
DOI: 10.1007/s10712-011-9144-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric Studies at the San Andreas Fault Zone: Implications for the Role of Fluids

Abstract: Fluids residing in interconnected porosity networks have a significant weakening effect on rheology of rocks and can strongly influence deformation along fault zones. The magnetotelluric (MT) technqiue is sensitive to interconnected fluid networks, and can image these zones on crustal and upper mantle scales. MT has imaged several prominent electrically conductive anomalies at the San Andreas fault which have been attributed to the presence of saline fluids within such networks, and which have been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 94 publications
3
35
0
Order By: Relevance
“…Analysis of the tipper is helpful as it provides a coarse but important indicator of 3D geo-electrical complexity and possible large-scale zonation for later inversion (Becken and Ritter 2012;Berdichevsky and Dmitriev 2008;Tietze and Ritter 2013). Figure 3 provides an example of one full tensor record from the Nevada data set, at station identifier 320 (see Fig.…”
Section: A Field Examplementioning
confidence: 99%
“…Analysis of the tipper is helpful as it provides a coarse but important indicator of 3D geo-electrical complexity and possible large-scale zonation for later inversion (Becken and Ritter 2012;Berdichevsky and Dmitriev 2008;Tietze and Ritter 2013). Figure 3 provides an example of one full tensor record from the Nevada data set, at station identifier 320 (see Fig.…”
Section: A Field Examplementioning
confidence: 99%
“…A review of intraplate earthquakes in Japan found clear imaging of lowvelocity zones and/or high-Vp/Vs zones near the rupture sources of many major earthquakes (Hasegawa et al 2009), presumably related to the presence of lower crustal fluid; however, velocity structure alone is not sufficient to infer the presence of fluids. Geomagnetic surveys have found regions of low resistivity near many active faults, which could relate to the presence of fluids in the source area (Gupta et al 1996;Tank et al 2005;Wannamaker et al 2009;Becken et al 2011;Becken and Ritter 2012). In Japan, some close relationships between low-resistivity regions and earthquake faults have been proposed (Mitsuhata et al 2001;Yamaguchi et al 2001;Uyeshima et al 2005;Yoshimura et al 2008).…”
Section: Relationship Between Fluids From the Mantle And The Generatimentioning
confidence: 99%
“…In Japan, some close relationships between low-resistivity regions and earthquake faults have been proposed (Mitsuhata et al 2001;Yamaguchi et al 2001;Uyeshima et al 2005;Yoshimura et al 2008). The characteristics of the relationships between faults and resistivity structures are summarized by Ogawa et al (2001) and Becken and Ritter (2012). Low-resistivity zones are generally located in the deeper parts of active faults and are thought to be caused by fluids.…”
Section: Relationship Between Fluids From the Mantle And The Generatimentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, magnetotelluric (MT) signals are an indication of the electrical resistivity of the Earth, a physical parameter that is highly sensitive not only to the temperature and bulk composition of rocks, but also to the presence and connectivity of melt, volatiles, and especially fluids (Hyndman and Shearer 1989;Becken and Ritter 2012). A great deal of effort has been made using MT soundings to obtain information on subsurface electrical conductivity anomalies around seismically active regions in subduction zones.…”
Section: Geophysical Observationsmentioning
confidence: 99%